2011
DOI: 10.1038/cmi.2011.7
|View full text |Cite
|
Sign up to set email alerts
|

Type I and II interferons enhance dendritic cell maturation and migration capacity by regulating CD38 and CD74 that have synergistic effects with TLR agonists

Abstract: The major limitation for the maturation of dendritic cells (DCs) using Toll-like receptor (TLR) agonists is their decreased ability to migrate into lymph nodes compared with conventional DCs. CD38 can be used as a multifunctional marker to modulate migration, survival and Th1 responses of DCs. CD74 has been shown to negatively regulate DC migration. The goal of this study was to investigate the combinations of TLR agonists and interferons (IFNs) that most effectively regulate CD38 and CD74 expression on DCs. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
27
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(30 citation statements)
references
References 26 publications
2
27
0
1
Order By: Relevance
“…Consequently, CD74 negatively regulates DC motility, perhaps, to allow more efficient sampling of antigens in the environment. Another study showed that IFN-␣ and IFN-␥ synergistically act with Toll-like receptor (TLR) agonists to downregulate CD74 and thus confer high migratory capacity on mature DCs (78). In this regard, increased CD74 levels may delay trafficking of T. gondii-infected cells to lymphoid organs, where an adequate immune response can be mounted.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, CD74 negatively regulates DC motility, perhaps, to allow more efficient sampling of antigens in the environment. Another study showed that IFN-␣ and IFN-␥ synergistically act with Toll-like receptor (TLR) agonists to downregulate CD74 and thus confer high migratory capacity on mature DCs (78). In this regard, increased CD74 levels may delay trafficking of T. gondii-infected cells to lymphoid organs, where an adequate immune response can be mounted.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the well characterized "conventional" type I IFNs such as IFNα subtypes and IFNβ, can regulate the development and activation of virtually every effector cell of the innate and adaptive immune response (2). Members of the type I IFN family of cytokines can promote survival of activated T and B cells (3,4), activate natural killer (NK) cells (5), induce MHC-I up-regulation (6) and provide signals for dendritic cell (DC) maturation (7,8). Their importance in host defense is underscored by the conservation of a multicomponent, species specific type I IFN family found throughout vertebrates.…”
mentioning
confidence: 99%
“…In addition, a reduction in the number of cytokines is needed to reduce the cost of cytokine maturation cocktails. We previously reported that combinations of TLR agonists and IFNs (IFN-α, IFN-γ) synergistically upregulated the expression of CD38 and CCR7, down-regulate CD74 expression, and induce the highest secretion of IL-12p70 [20]. Based on these results, we generated potent DCs (VAX-DC/MM) with high production of IL-12p70 and good migration capacity.…”
Section: Discussionmentioning
confidence: 99%